Informal settlements: A divis\~ao da cidade e seus termos - Renato Nunes Balbim; Cristine Diniz Santiago (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This is the first of a series of four Discussion Papers (DP) that are part of the survey How cities are divided: the invention of informal settlements. The goal of this series of DPs was to carry out a culturomic and scientometric study on the use of the term informal settlements contextualized by previous geopolitical and public policies analysis. Specifically in this DP, a historical, theoretical-conceptual discussion is presented, which is needed for understanding the diffusion and use of the term, related to dualisms and ideas that contribute to the reinforcement of the idea of a divided city and its unequal structures. It also discusses the formation of hot research agendas and how they reinforce articulations between science and policies propagated by international agencies that feed back each other. Finally, essential methodological information is provided for understanding why the culturomic, scientometric and bibliometric analyzes presented in the two subsequent DPs are presented, as well as the databases used, their limits and potential. Thus, in this introductory volume, we sought not only to synthesize the historical, theoretical and conceptual foundations of this specific research that makes up the study How cities divided: the invention of informal settlements, but also to relate them objectively to what will be presented in the other volumes that make up this series.
10419/284889
Keywords: R28; H76; O18; 330; informal settlements; urban management; bibliometric analysis; favela; divided city